3y + 4z + 12y = 3y
-3y -3y
-------------------------
4z + 12y = 0
divide everything by 4
z + 3y = 0
-3y -3y
z = -3y
5x-2y+3z-2x-y-4z=3x-3y-z
9x + 3y + 5z - 5x + 4z - 7y = 4x - 4y + 9z
-8z + 12 = 12 - 4z-8z +4z + 12 = 12 - 4z +4z-4z + 12 -12 = 12 -12-4z / -4 = 0 / -4z = 0:)
6z-4z-z = 6-7-4 z = -5
(z=-3) and (z=7)
its 10x +9y +1z
5x-2y+3z-2x-y-4z=3x-3y-z
9x + 3y + 5z - 5x + 4z - 7y = 4x - 4y + 9z
3x-3y+7z
There are 3 terms in the given expression
-8z + 12 = 12 - 4z-8z +4z + 12 = 12 - 4z +4z-4z + 12 -12 = 12 -12-4z / -4 = 0 / -4z = 0:)
9z
== ==
7 + 4z = 437 + 4z -7 = 43 - 7 4z = 43 - 7 4z = 36 z = 9
10x2 - 20xz + 15xy = 5x (2x - 4z + 3y)
6z-4z-z = 6-7-4 z = -5
-6z 2 = 3z+ 4z+28 -6z+2 +3z = 3z+ 4z +28 +4z -6z+4z+2 = 3z+ 28 -10z+2 -3z= 28 - 2 -10z + -3z = 26 -13z/13 = 26/-13 z = -2